UV Rays, the prooxidant/antioxidant imbalance in the cornea and oxidative eye damage - Cejková, J; Stípek, S; Crkovská, J; Ardan, T; Pláteník, J; Cejka, C; Midelfart, A (Physiological research, 2004)
In this minireview, the factors involved in the development of corneal injury due to an increased amount of UVB rays are summarized. Experimental studies have shown that an increased number of UVB rays leads to a profound decrease in corneal antioxidants (high molecular weight, antioxidant enzymes as well as low molecular weight, mainly ascorbic acid) so that a prooxidant/antioxidant imbalance appears. The decrease of corneal antioxidant protective mechanisms results in oxidative injury of the cornea and causes damage of the inner parts of the eye by UVB rays and by reactive oxygen species generated by them.
Keywords: nemoci rohovky; Ultraviolet Rays; ultrafialové záření; Oxidants; antioxidancia; Corneal Diseases; Animals; lidé; Antioxidants; rohovka; Cornea; zvířata; Humans; oxidancia